2021
DOI: 10.1038/s41598-021-01538-2
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis and characterization of Fe3O4 nanoparticles using Chlorella-K01 extract for potential enhancement of plant growth stimulating and antifungal activity

Abstract: The purpose of this research was to determine the efficacy of iron oxide nanoparticles (Fe3O4-NPs) using microalgal products as a plant growth stimulant and antifungal agent. The work was conducted with the phyco-synthesis and characterization of Fe3O4-NPs using 0.1 M ferric/ferrous chloride solution (2:1 ratio; 65 °C) with aqueous extract of the green microalga Chlorella K01. Protein, carbohydrate and polyphenol contents of Chlorella K01 extract were measured. The synthesized microalgal Fe3O4-NPs made a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(29 citation statements)
references
References 40 publications
5
14
0
Order By: Relevance
“…Different concentrations 10, 40 and 80 mg L −1 of Fe 3 O 4 /HA NPs significantly ( p < 0.05) reduced the mycelial growth of A. striticum over the control. Our finding is supported by earlier studies that exhibited the antimicrobial activity of Fe 3 O 4 and HA against fungal and bacterial agents [ 56 , 57 , 58 , 59 , 60 , 61 ]. Iron oxide NPs have not only been shown to boost the plant growth but also exhibit the antifungal activities against a variety of fungal pathogens [ 58 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Different concentrations 10, 40 and 80 mg L −1 of Fe 3 O 4 /HA NPs significantly ( p < 0.05) reduced the mycelial growth of A. striticum over the control. Our finding is supported by earlier studies that exhibited the antimicrobial activity of Fe 3 O 4 and HA against fungal and bacterial agents [ 56 , 57 , 58 , 59 , 60 , 61 ]. Iron oxide NPs have not only been shown to boost the plant growth but also exhibit the antifungal activities against a variety of fungal pathogens [ 58 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our finding is supported by earlier studies that exhibited the antimicrobial activity of Fe 3 O 4 and HA against fungal and bacterial agents [ 56 , 57 , 58 , 59 , 60 , 61 ]. Iron oxide NPs have not only been shown to boost the plant growth but also exhibit the antifungal activities against a variety of fungal pathogens [ 58 ]. In the poisoned food technique, iron NPs inhibited the mycelial growth of Alternaria alternata up to 87.9% at a 1.0 mg mL −1 concentration [ 62 ].…”
Section: Discussionsupporting
confidence: 92%
“…Reportedly, α-Fe 2 O 3 could be synthesized using several biological substance agents, such as extract of Citrus reticulum peels, 153 Aloe vera leaf, 154 Spondias dulcis leaf, 155 Carica papaya leaf, 120 Gardenia resinifera plant, 156 Curcuma and tea leaves, 157 Sida cordifolia plant, 158 and Bridelia retusa leaf. 159 As for the synthesis of Fe 3 O 4 , several biological substance agents were used such as aqueous extracts of zanthoxylum armatum dc leaf, 160 Rhus coriaria, 161 Graptophyllum pictum leaf, 162 Chlorella-k01, 163 seaweed (Kappaphycus alvarezii), 164 Garcinia mangostana fruit peel, 165 gundelia tournefortii l plant., 166 Punica granatum l. of fruit peel, 167 biosurfactant Saccharum of ficinarum, 168 Azadirachta indica, 169 rambutan peel waste, 170 α-D-glucose, and gluconic acid. 171 Green synthesis even could be used to obtain metastable iron oxides, 147,172 for instance, β-Fe 2 O 3 nanoparticles synthesized using a simple chemical method from a mixture of FeCl 3 solution and Iraqi grape extract 172 and β-Fe 2 O 3 nanoparticles synthesized from a Fe 3+ salt and Cammelia sinensis (black tea) extract using heat treatment.…”
Section: Nanometer-sized Ironmentioning
confidence: 99%
“…Reportedly, α-Fe 2 O 3 could be synthesized using several biological substance agents, such as extract of Citrus reticulum peels, Aloe vera leaf, Spondias dulcis leaf, Carica papaya leaf, Gardenia resinifera plant, Curcuma and tea leaves, Sida cordifolia plant, and Bridelia retusa leaf . As for the synthesis of Fe 3 O 4 , several biological substance agents were used such as aqueous extracts of zanthoxylum armatum dc leaf, Rhus coriaria , Graptophyllum pictum leaf, Chlorella-k01 , seaweed ( Kappaphycus alvarezii ), Garcinia mangostana fruit peel, gundelia tournefortii l plant., Punica granatum l . of fruit peel, biosurfactant Saccharum officinarum , Azadirachta indica , rambutan peel waste, α- d -glucose, and gluconic acid .…”
Section: Advance Fabrication Of Nanometer-sized Iron Oxides From Natu...mentioning
confidence: 99%
“…Tovar et al (2020) evaluated the effects of biogenic iron nanoparticles on corn germination and found positive results such as a higher germination index and an increase in root and shoot length [ 23 ]. Win et al (2021) observed an increase in the germination index of rice, corn, mustard, green gram, and watermelon seeds treated with biogenic iron nanoparticles [ 24 ].…”
Section: Introductionmentioning
confidence: 99%